The Role of Gut-Brain-Skin Axis in Guttate Psoriasis caused by Enterobacter cloacae - Cut Putri Hazlianda; Molla Andriska Dewi (Talenta Publisher, 2026)
Background: Background: Psoriasis is a chronic inflammatory skin condition often manifesting as erythematous plaques with white scales. Guttate psoriasis (GP), a specific variant, presents as sudden-onset red, water-drop-like spots typically triggered by infections. The gut-brain-skin axis highlights the role of gut microbiota in modulating skin inflammation. Objectives: To present a case report of guttate psoriasis and the interplay between gut-brain-skin axis in guttate psoriasis. Case Presentation: A 28-year-old woman presented with itchy raised red patches covered by thick white scales. Symptoms began a month earlier, with red spots first appearing on her chest and spreading. A week prior, she experienced fever, sore throat, nausea, vomiting, and diarrhea. Physical examination revealed erythematous papules and plaques with positive Auspitz and Karsvlek signs. A throat swab identified Enterobacter cloacae. Treatment included cetirizine, hydrocortisone cream, desoximetasone cream, and ketoconazole shampoo. Discussion: The gut-brain-skin axis suggests that gut microbiota, like Enterobacter cloacae, can affect skin inflammation through immune modulation. Dopamine produced by gut bacteria may exacerbate psoriasis by influencing T cells and keratinocytes. Stress also plays a role in psoriasis flare-ups. This patient’s history of bacterial infection and stress supports this theory. Conclusion: This case illustrates the intricate interplay between gut microbiota, stress, and immune mechanisms in GP, emphasizing the need for holistic treatment approaches in managing psoriasis. Keyword: Enterobacter cloacae, Gut, Guttate psoriasis, Microbiota, Skin axis Latar Belakang: Psoriasis adalah kondisi peradangan kulit kronis yang sering bermanifestasi sebagai plak eritematosa dengan sisik putih. Psoriasis gutata (GP) adalah varian khusus yang muncul sebagai bintik merah yang menyerupai tetesan air dengan onset tiba-tiba yang biasanya dipicu oleh infeksi. Tujuan: Untuk mempresentasikan laporan kasus psoriasis gutata dan hubungan pola antara aksis saluran pencernaan-otak-kulit di psoriasis gutata. Presentasi kasus: Seorang wanita berusia 28 tahun datang dengan keluhan bercak merah gatal yang menonjol dan tertutup sisik putih tebal. Gejala muncul sejak satu bulan sebelumnya, dimulai dengan bintik merah di dada yang kemudian menyebar. Seminggu sebelum munculnya lesi, pasien mengalami demam, sakit tenggorokan, mual, muntah, dan diare. Pemeriksaan fisik menunjukkan papul dan plak eritematosa dengan tanda Auspitz dan Karsvlek yang positif. Hasil kultur usap tenggorokan mengidentifikasi Enterobacter cloacae. Pasien diberikan terapi berupa cetirizine, krim hidrokortison, krim desoximetasone, dan sampo ketokonazol. Pembahasan: Aksis saluran pencernaan-otak-kulit menunjukkan bahwa mikrobiota usus, seperti Enterobacter cloacae, dapat memengaruhi inflamasi kulit melalui modulasi sistem imun. Dopamin yang diproduksi oleh bakteri usus berpotensi memperburuk psoriasis dengan memengaruhi sel T dan keratinosit. Stres juga berperan dalam kekambuhan psoriasis. Riwayat infeksi bakteri dan stres pada pasien ini mendukung teori tersebut. Kesimpulan: Kasus ini menggambarkan hubungan antara mikrobiota usus, stres, dan mekanisme imun dalam GP, sehingga menekankan pentingnya pendekatan terapi holistik dalam tata laksana psoriasis. Kata Kunci: Aksis kulit, Enterobacter cloacae, Mikrobiota, Psoriasis gutata, Usus